2002
DOI: 10.1590/s0102-79722002000100009
|View full text |Cite
|
Sign up to set email alerts
|

Construção da taxonomia brasileira para descritores da personalidade

Abstract: Os estudos referentes à avaliação psicológica no Brasil apresentam dificuldades básicas em seu desenvolvimento. Um dos principais problemas apresentados pelos autores diz respeito à qualidade e quantidade de instrumentos de avaliação disponíveis para a realidade brasileira. (Andriola,

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2014
2014
2018
2018

Publication Types

Select...
1
1
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(4 citation statements)
references
References 6 publications
(7 reference statements)
0
4
0
Order By: Relevance
“…Several of the terms listed in Appendix 2 of this manuscript, for example, do not appear in lists of descriptors, such as those carefully elaborated by the team responsible for the first psycholexical study which used as the data source a Brazilian dictionary (Guzzo & Carvalho, 2002;Pinho & Guzzo, 2003). In this study we found a great number of adjectives such as grudento (sticky), hiperativo (hyperactive), enganador (deceitful),…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Several of the terms listed in Appendix 2 of this manuscript, for example, do not appear in lists of descriptors, such as those carefully elaborated by the team responsible for the first psycholexical study which used as the data source a Brazilian dictionary (Guzzo & Carvalho, 2002;Pinho & Guzzo, 2003). In this study we found a great number of adjectives such as grudento (sticky), hiperativo (hyperactive), enganador (deceitful),…”
Section: Resultsmentioning
confidence: 99%
“…The research of the Brazilian group (Guzzo, Pinho, & Carvalho, 2002;Pinho, 2005;Pinho & Guzzo, 2003) was carried out in five subsequent stages, basically involving analyses made by judges: (i) selection of all 35,834 adjectives from one Brazilian Portuguese dictionary of 1996 (Guzzo et al, 2002); (ii) selection of personality descriptive adjectives by two judges graduating in psychology, according to 11 exclusion criteria inspired in , resulting in 5,774 words (Guzzo et al, 2002;Pinho & Guzzo, 2003); (iii) the classification and selection of the remaining adjectives from the second stage, following the criteria of the usefulness of the adjective for personality description, frequency of use in professional practice, and clarity, resulting in a list of 938 words; and (iv) classification of the adjectives of this list in the categories of tendencies, social aspects, physical characteristics or appearance, temporary states or conditions, and terms of limited utility (Pinho, 2005). No other study that has sequenced this project was identified in a search in the Brazilian Virtual Health Library of Psychology (2016).…”
Section: The Research With the Lexical Hypothesis In Brazilmentioning
confidence: 99%
“…Several of the terms listed in Appendix 2 of this manuscript, for example, do not appear in lists of descriptors, such as those carefully elaborated by the team responsible for the first psycholexical study which used as the data source a Brazilian dictionary (Guzzo & Carvalho, 2002;Pinho & Guzzo, 2003). In this study we found a great number of adjectives such as grudento (sticky), hiperativo (hyperactive), enganador (deceitful), desnaturado [denatured], etc.…”
Section: Discussionmentioning
confidence: 99%
“…Only one Brazilian initiative was identified that followed the procedure of initiating the construction of a personality taxonomy starting from the examination of a dictionary. The research of the Brazilian group (Guzzo, Pinho, & Carvalho, 2002;Pinho, 2005;Pinho & Guzzo, 2003) was carried out in five subsequent stages, basically involving analyses made by judges: (i) selection of all 35,834 adjectives from one Brazilian Portuguese dictionary of 1996 (Guzzo et al, 2002); (ii) selection of personality descriptive adjectives by two judges graduating in psychology, according to 11 exclusion criteria inspired in , resulting in 5,774 words (Guzzo et al, 2002;Pinho & Guzzo, 2003); (iii) the classification and selection of the remaining adjectives from the second stage, following the criteria of the usefulness of the adjective for personality description, frequency of use in professional practice, and clarity, resulting in a list of 938 words; and (iv) classification of the adjectives of this list in the categories of tendencies, social aspects, physical characteristics or appearance, temporary states or conditions, and terms of limited utility (Pinho, 2005). No other study that has sequenced this project was identified in a search in the Brazilian Virtual Health Library of Psychology (2016).…”
Section: The Research With the Lexical Hypothesis In Brazilmentioning
confidence: 99%